2012
DOI: 10.1029/2012ja017611
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of galactic cosmic ray models

Abstract: [1] Among several factors involved in the development of a manned space mission concept, the astronauts' health is a major concern that needs to be considered carefully. Galactic cosmic rays (GCRs), which mainly consist of high-energetic nuclei ranging from hydrogen to iron and beyond, pose a major radiation health risk in long-term space missions. It is therefore required to assess the radiation exposure of astronauts in order to estimate their radiation risks. This can be done either by performing direct mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 52 publications
3
42
0
Order By: Relevance
“…This model choice is strongly motivated by the wide availability of the model itself and supported by the good agreement found between the re-normalized ALTEA data and the DOSTEL data. Weaknesses of the CREME96 model have been nevertheless pointed out in recent works (see, e.g., Mrigakshi et al 2012). Further work is in progress to test the sensitivity of this re-normalization on the chosen model, by using more performing tools such as Badhwar/O'Neill (O'Neill et al 2015) or DLR (Matthiä et al 2013) models.…”
Section: Discussionmentioning
confidence: 99%
“…This model choice is strongly motivated by the wide availability of the model itself and supported by the good agreement found between the re-normalized ALTEA data and the DOSTEL data. Weaknesses of the CREME96 model have been nevertheless pointed out in recent works (see, e.g., Mrigakshi et al 2012). Further work is in progress to test the sensitivity of this re-normalization on the chosen model, by using more performing tools such as Badhwar/O'Neill (O'Neill et al 2015) or DLR (Matthiä et al 2013) models.…”
Section: Discussionmentioning
confidence: 99%
“…A review paper on these commonly used GCR models has recently been published by Mrigakshi , et al . []. As noted, selecting a GCR model appropriate for the epoch when the measurements are made is a key for the accurate estimate of GCR‐induced neutron environment.…”
Section: Numerical Modeling—input Parametersmentioning
confidence: 99%
“…A comparison of different GCR models is described in Usoskin et al [2005], where a way was suggested to relate one model to another. A review paper on these commonly used GCR models has recently been published by Mrigakshi, et al [2012]. As noted, selecting a GCR model appropriate for the epoch when the measurements are made is a key for the accurate estimate of GCR-induced neutron environment.…”
Section: Gcr Environment Modelmentioning
confidence: 99%
“…The solar modulation potential is a modeling parameter which is based on ground measurements and depends on the choice of the local interstellar spectrum (LIS) model. In the past LIS spectra have been established in many ways (Burger et al, ; Mrigakshi et al, ) and the Burger‐Usoskin LIS spectrum was considered in this work (Usoskin et al, ). However, the physical interpretation of the modulation potential is not straightforward during periods of active Sun (Usoskin et al, ) and requires more refined physical analyses.…”
Section: Analyses Of Fds and Gle Based On Neutron Fluxesmentioning
confidence: 99%
“…The standard methods to determine ϕ(t) are based on NMs, whose advantages are the existence of an worldwide network, the efficient integration time (typically t int > 1 min) and the high coverage of the geomagnetic latitudes using one of the several yield functions calculated in the literature (Clem & Dorman, ; Flückiger et al, ; Mangeard et al, ; Mishev et al, ; Nagashima, ). As previously described, ϕ(t) depend on models for the Berger‐Usoskin LIS spectrum (Mrigakshi, ). Monthly averaged modulation parameters from 1951 are available (Herbst et al, ; Usoskin et al, ; Usoskin et al, ), using several LISs and several NMs.…”
Section: Analyses Of Fds and Gle Based On Neutron Fluxesmentioning
confidence: 99%